Effect of ageing on hypoxic exercise cardiorespiratory, muscle and cerebral oxygenation responses in healthy humans. Issue 4 (28th February 2017) - Puthon, Lara; Bouzat, Pierre; Robach, Paul; Favre‐Juvin, Anne; Doutreleau, Stéphane; Verges, Samuel
Abstract : New Findings: What is the central question of this study? This study aimed to determine the effect of ageing on cardiorespiratory and tissue oxygenation responses to hypoxia during maximal incremental exercise. What is the main finding and its importance? Older healthy subjects had preserved hypoxic cardiorespiratory and tissue oxygenation responses at rest and during moderate exercise. At maximal exercise, they had a reduced hypoxic ventilatory response but similar maximal power output reduction compared with young individuals. This study suggests that until moderate exercise, hypoxic responses are preserved until the age of 70 years and therefore that ageing is not a contraindication for high‐altitude sojourn. This study assessed the effects of ageing on cardiorespiratory and tissue oxygenation responses to hypoxia both at rest and during incremental maximal exercise. Sixteen young (20–30 years old) and 15 older healthy subjects (60–70 years old) performed two maximal incremental cycling tests in normoxia and hypoxia (inspiratory oxygen fraction 12%). Cardiorespiratory responses, prefrontal cortex and quadriceps tissue oxygenation (near‐infrared spectroscopy) were measured during exercise as well as during hypercapnia at rest. The hypoxic ventilatory response was similar in young compared with older individuals at rest and during moderate‐intensity exercise (50% maximal power output: young 0.9 ± 0.2 versus older 1.1 ± 0.8 l min −1  % −1 ; P  > 0.05) but larger in young subjects during high‐intensity exercise (maximal power output: 2.2 ± 0.8 versus 1.8 ± 1.1 l min −1  % −1 ; P  < 0.05). The hypoxic cardiac response did not differ between groups both at rest and during exercise. During exercise in hypoxia, young subjects showed greater deoxygenation than older subjects, at both the prefrontal cortex and quadriceps levels. The hypoxia‐induced reduction in maximal power output (young −32 ± 5% versus older −30 ± 6%; P  > 0.05) and the hypercapnic responses did not differ between groups. Older healthy and active individuals below the age of 70 years have cardiorespiratory and tissue oxygenation responses to hypoxia similar to young individuals both at rest and during moderate‐intensity exercise. Despite a lower hypoxic ventilatory response at maximal exercise, older individuals have similar oxygen desaturation and maximal power output reduction compared with young subjects. Abstract :